Insecticidal potential of five medicinal plants: An In Vitro evaluation and molecular docking analysis of Artemisia absinthium. - Mohd Yaseen; Mudasir Gani; Shabir Ahmad Ganai; Baseerat Ul Ann; Fehim Jeelani Wani; Mohd Ayoub Mantoo; Khalid Rasool; Rashid Mumtaz Khan (PLoS ONE, 2025)
The Kashmir range of North-Western Himalayas harbours a large number of medicinal plants that have insecticidal, antifeedent or insect repellent properties. Herein, we evaluated the insecticidal activity of five medicinal plants including Artemisia absinthium, Acorus calamus, Digitalis purpurea, Plectranthus rugosus and Achiella millefolium against Corcyra cephalonica, Sitophilus oryzae and Helicoverpa armigera. The highest in vitro insecticidal activity was observed with the A. absinthium plant extract against the test insects. Following this, A. absinthium extract was assessed through high resolution liquid chromatography mass spectrometry (HR-LCMS). The small molecules thus identified from the A. absinthium extract were flexibly docked against the active site of acetylcholinesterase (Helicoverpa armigera) keeping the known inhibitor malaoxon as the reference. Four molecules encompassing kaempferol, diosmetin, 1,7-Bis(4-hydroxyphenyl) heptan-3-one and NP-021018 explored from the defined extract manifested the highest binding affinity than malaoxon. As kaempferol evinced the maximum binding activity towards acetylcholinesterase thus, the insecticidal activity of A. absinthium extract may be attributed to this molecule.